1999
DOI: 10.1177/096368979900800604
|View full text |Cite
|
Sign up to set email alerts
|

Xenografting Human T2 Sympathetic Ganglion from Hyperhidrotic Patients Provides Short-Term Restoration of Catecholaminergic Functions in Hemiparkinsonian Athymic Rats

Abstract: Previous studies have suggested that allografting peripheral sympathetic ganglia, such as superior cervical ganglia, partially relieves clinical or behavioral deficits in parkinsonian patients and animals. However, removal of these ganglia can cause Homer's syndrome, which limits the utilization of this approach. Hyperhidrosis, a disease of excessive sweating, is commonly seen in young Orientals. Treatment of hyperhidrosis often involves surgical removal of the second thoracic sympathetic ganglia (T2G), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…We found that treatment with PFT- α for 5 days significantly improved the survival of grafts, enhanced their viability and potentiated functional recovery of hemiparkinsonian animals. Our results differ from a previous study showing that the peptide caspase inhibitor, Ac-YVADCMK, which has minimal blood-brain barrier permeability, did not augment survival of TH-ir neurons in VM grafts (14). In Marchinoni’s study, Ac-YVAD-CMK was added to the graft cell suspension only prior to transplantation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that treatment with PFT- α for 5 days significantly improved the survival of grafts, enhanced their viability and potentiated functional recovery of hemiparkinsonian animals. Our results differ from a previous study showing that the peptide caspase inhibitor, Ac-YVADCMK, which has minimal blood-brain barrier permeability, did not augment survival of TH-ir neurons in VM grafts (14). In Marchinoni’s study, Ac-YVAD-CMK was added to the graft cell suspension only prior to transplantation.…”
Section: Discussioncontrasting
confidence: 99%
“…Rotational behavior (14,15) was evaluated using a multichannel rotometer system (RotoMax, AccuScan Instruments, Inc). Animals were individually placed in the test cylinder.…”
Section: Methodsmentioning
confidence: 99%
“…Rotational behavior [42,43] was evaluated using a multichannel rotometer system (RotoMax, AccuScan Instruments, Inc). Six days after 6-OHDA lesioning, all animals were challenged with methamphetamine (2.5 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the allogenic grafts, human dopaminergic cells have been grafted to 6-OHDA-lesioned rats. [456] To ensure the survival of xenografts in the host brain, the immunosuppressive agent cyclosporine A (CsA) was used as an adjunctive therapy to avoid xenograft rejection. [5] Chronic treatment with CsA improved the survival and function of transplanted human fetal ventromesencephalic cells in 6-OHDA-lesioned rats.…”
Section: Transplantation Of Human Dopaminergic Cells To 6-hydroxydopamentioning
confidence: 99%